The PCA Ruling and ASEAN: A Call for Unity - Liow, Joseph Chinyong (2016)
The much-awaited ruling of the Permanent Court of Arbitration on the maritime dispute in the South China Sea between the Philippines and China was finally delivered. Taken together, it was nothing short of a comprehensive rejection of Chinese claims. As expected, China has summarily rejected the decision. How will ASEAN deal with a defiant China?